Changes in the neurologists’ professional identity - Šeduikienė , M.; Matonis , V. (Neurologijos seminarai, 2020)
Introduction. Neurologists’ professional identity (NPI) experiences constant changes due to rapid development of neurology innovations, whereas neither concept nor peculiarities of NPI changes have been investigated in literature, at least to the best knowledge of the authors, excluding the descriptions of some aspects of the concept.Objective. To reveal NPI peculiarities and make analysis of assumptions that can cause their changes.Tasks. To propose the definition of NPI and evaluate how both the IT and neurology innovations are impacting changes of NPI.Methods. Review of the latest literature, as well as the application of prognostic method to estimate NPI changes in future. The proposal of NPI definition is based on a variety of NPI characteristics presented in literature. Main assumptions of NPI changes are differentiated and described.After summarizing various approaches, the definition of NPT was formulated and assumptions determining the changes in NPT were identified and described. Using a predictive method based on the analysis of the impact of IT, biotechnology and medical innovations on neurology, possible future changes in NPT were discussed.Results and discussion. The results of the investigation and discussions are introduced in five paragraphs.In the first paragraph The concept of NPI, peculiarities of its formation and changes, the definition of NPI is presented and effect of NPI changes on neurologist’s sense of well-being is elucidated.In the second paragraph Development of technologies and enlargement of neurologist’s possibilities, the impact of computation and robotics on NPI changes is considered and neurologists’ preparedness to meet new challenges is examined.The third paragraph The influence of medical innovations on NPI changes explains the necessity to obtain some new competences arising from epidemic growth of chronic diseases which, in turn, increase the number of subspecialties.The fourth paragraph The impact of overlap of neurology with adjacent professions on NPI changes discloses situations where neurologists in some aspects overlap with adjacent professions and may solve some therapeutic problems that are intensively emerging in some domains of contemporary social life, such as psychedelic therapy, creation of global happiness, and enhancing student achievement.In the fifth paragraph Prognostic insights of neurology and possible changes in NPI, some discussions on possible future changes in NPI are considered.Conclusions. Key findings and essential features of the discussion are summarized in the conclusion paragraph. NPI peculiarities and factors which cause their changes are highlighted as well as it is shown how NPI content understanding may strengthen neurologist’s professional self-perception.
Keywords: neurologists’ professional identity; innovations in neurology; neurologic subspecialties